Contamination Measurements from Simultaneous Activated Potassium Bromide Radiological Dispersal Devices with a Collimated Vehicular Sensor. Issue 6 (June 2021) - Simerl, Nathanael; Beavers, Jace; Milburn, Jacob; Dodson, Miranda; Strahler, Ryan; Kroeger, Richard; Ulloa-Garcia, Ivan; Moosman, Bryan; Sin, Terence; Kagan, Jeffrey; Nelson, Kyle; Paradis, Nathan; et al.
Abstract : Abstract: Surface contamination was quantified over a distributed source of activated potassium bromide from three detonations of Radiological Dispersal Devices (RDDs) at the Idaho National Laboratory Radiological Response Training Range, with a maximum sampled area of 19, 900 m 2, to provide a baseline comparison with other rapid, remote mapping methods. Measurements were obtained with a cerium bromide sensor collimated to a field of view of 3.14 m 2, using lead shielding, and towed behind a ground vehicle. Sensor response correction factors for activated potassium bromide were calculated through simulation with SWORD to obtain activity per meter-squared. Continuous maps were produced by interpolating coverage from lawnmower raster scans. Radiological data was overlaid with aerial imagery from an automated unmanned aerial vehicle flight to provide contextual geological information relative to contamination levels. The contamination distribution measurements will be compared to unmanned aerial vehicle methods in future work.